Uji Aktivitas Antioksidan Ekstrak Buah Merah (Pandanus baccari L) Di Daerah Poso Sulawesi Tengah - Sangkala, Serti A.; Jura, Minarni Rama; Tangkas, I Made (Jurnal Akademika Kimia, 2014)
Research on the antioxidant activity test has been done on red fruit (pandanus baccari L) from Poso area Central Sulawesi. This research was conducted by laboratory experiments using maceration extraction techniques, DPPH (1,1-diphenyl-2-pikrilhidrazil) as free radicals, vitamin C as positive control, UV-Vis spectronic as a tool for antioxidant test, and red fruit extracts as samples. The aim of this research was to determine antioxidant strength of red fruit extracts. The red fruit sample was used as much as 30 grams, and the solvent was an absolute ethanol, whereas variations in the concentration of red fruit extracts used were 20 ppm, 40 ppm, 60 ppm, and 80 ppm. Antioxidant activity test was done by using a UV-Vis spectronic and IC50. The results showed that the red fruit extracts had strong antioxidant activity with the percentage of optimum activity in inhibiting free radical by 81.02%, and the IC50 value was 14.454 ppm.